2015
DOI: 10.21608/mnj.2015.149134
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Management of Their Children With Epilepsy

Abstract: Epilepsy is a chronic neurological disorder, characterized by recurrent unprovoked seizures. Epilepsy starts in childhood in 60% of cases and most of the clinically significant aspects of the disease occur during childhood. Parents, especially the mothers, play the most significant role in helping their epileptic children adapt to their condition. This study aimed to assess mothers' management of their epileptic children. The study was conducted at the Epileptic Clinic of Mansoura University Children Hospital.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Surprisingly, male parents showed significantly high awareness, whereas a significant proportion of female parents showed low awareness, although it was well known that mothers were the people responsible for the care of children. In a previous study on mothers, it was demonstrated that one-half of mothers had total management scores in managing their epileptic children, and these were either good or satisfactory [Badawy, 2015].…”
Section: Discussionmentioning
confidence: 97%
“…Surprisingly, male parents showed significantly high awareness, whereas a significant proportion of female parents showed low awareness, although it was well known that mothers were the people responsible for the care of children. In a previous study on mothers, it was demonstrated that one-half of mothers had total management scores in managing their epileptic children, and these were either good or satisfactory [Badawy, 2015].…”
Section: Discussionmentioning
confidence: 97%